1985
DOI: 10.1029/rs020i004p00907
|View full text |Cite
|
Sign up to set email alerts
|

ZDR measurement considerations for a fast scan capability radar

Abstract: This paper discusses the possibility of incorporating differential reflectivity (ZDR) measurement in Doppler radars having fast scan capability, without compromising the accuracy of the spectral moment estimates. The presently established technique of ZDR measurement using alternate sampling of horizontally and vertically polarized signals (H and V) has long acquisition time and reduced maximum unambiguous velocity. It is shown that ZDR acquisition time can be reduced significantly by simultaneously sampling H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 10 publications
2
49
0
Order By: Relevance
“…Canting and scattering properties are of minimal concern in light rain and drizzle due to the mainly spherical shape of the small drops. Theoretical values of ρ HV larger than 0.99 are indicated by Sachidananda and Zrnic (1985) because of the small shape effects in rain, but theory does not account for possible decreases due to sidelobes and receiver noise.…”
Section: Data Qualitymentioning
confidence: 99%
“…Canting and scattering properties are of minimal concern in light rain and drizzle due to the mainly spherical shape of the small drops. Theoretical values of ρ HV larger than 0.99 are indicated by Sachidananda and Zrnic (1985) because of the small shape effects in rain, but theory does not account for possible decreases due to sidelobes and receiver noise.…”
Section: Data Qualitymentioning
confidence: 99%
“…This is defined as (Sachidananda and Zrnić 1985). The is therefore useful for identifying non-rain hydrometeors.…”
Section: Copolar Correlation Coefficient (Dimensionless)mentioning
confidence: 99%
“…Gourley et al (2006) reported ρ HV (0) peak values in rain better than 0.99 for the Trappes radar with a sample number of 23 and a time resolution of 15 min. More recently, Yamauchi et al (2012) reported ρ HV (0) peak values of 0.998, which implies the use of a surprisingly reliable radar, as this value is very close to the theoretical expectation of 0.999 for drops without oscillation A. Adachi et al: Detection of potentially hazardous convective clouds 2743 (Sachidananda and Zrnić, 1985). Additionally, they recorded this peak value with a sample number of 20, which enabled volumetric scans with a time resolution of 4 minutes for their system.…”
Section: A Adachi Et Al: Detection Of Potentially Hazardous Convectmentioning
confidence: 87%
“…Sachidananda and Zrnić (1985) showed that reliable polarimetric data can be obtained from 50 simultaneous samples when ρ HV (0) > 0.995 and the spectrum width > 4 m s −1 . The value of ρ HV (0) measured with polarimetric radars has been increasing with the advent of innovative radar technology.…”
Section: A Adachi Et Al: Detection Of Potentially Hazardous Convectmentioning
confidence: 99%